2007
DOI: 10.1038/sj.gene.6364416
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of naïve and subsets of memory CD4+ and CD8+ T cells to hydrogen peroxide-induced apoptosis

Abstract: CD4 þ and CD8 þ memory T cells are identified into central and effector memory subsets, which are characterized by distinct homing patterns and functions. In this investigation, we show that naïve and central memory CD4 þ and CD8 þ T cells are sensitive to hydrogen peroxide (H 2 O 2 )-induced apoptosis, whereas effector memory CD4 þ and CD8 þ T cells are relatively resistant to H 2 O 2 -induced apoptosis. Apoptosis in naïve and central memory CD4 þ and CD8 þ is associated with the release of cytochrome c and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Furthermore, if arginase activity is inhibited at the time of PMN activation, the proportion of non‐viable T cells is further increased via a process also involving H 2 O 2 generation. Differential sensitivity of T‐cell subsets to H 2 O 2 ‐mediated cell death has been reported previously and may explain why only a proportion of T cells were susceptible to PMN act ‐mediated cell death . This differential sensitivity may also explain why the presence of ABAH, which inhibits a major pathway of H 2 O 2 consumption and may therefore increase its levels, induced increased cell death in pre‐activated cells but not purified circulating T cells.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, if arginase activity is inhibited at the time of PMN activation, the proportion of non‐viable T cells is further increased via a process also involving H 2 O 2 generation. Differential sensitivity of T‐cell subsets to H 2 O 2 ‐mediated cell death has been reported previously and may explain why only a proportion of T cells were susceptible to PMN act ‐mediated cell death . This differential sensitivity may also explain why the presence of ABAH, which inhibits a major pathway of H 2 O 2 consumption and may therefore increase its levels, induced increased cell death in pre‐activated cells but not purified circulating T cells.…”
Section: Discussionmentioning
confidence: 56%
“…According to the results by Takahashi et al (169), a higher expression of the GSH molecule has been found in the naive T-cell subset as compared with the memory T-cell subset (46). Different results were reported by Gupta et al (57), who observed that H 2 O 2 induced apoptosis preferentially in naive T cells and central memory T cells as compared with effector memory T cells via a reduction in GSH levels. Overall, these data, although contrasting, show that distinct T-cell subsets have differential susceptibility to oxidative stress-induced apoptosis, and this susceptibility is associated with intracellular GSH.…”
Section: Oxidative Stress and Apoptosis In Autoimmunitymentioning
confidence: 76%
“…Given that H 2 O 2 induces also necrosis and mediates apoptosis primarily via a caspase-dependent pathway [39], [40], we performed experiments with Z-VAD-FMK. A pre-treatment with Z-VAD-FMK prevented DCIR expression in activated CD4 + T cells after H 2 O 2 stimulation (i.e.…”
Section: Resultsmentioning
confidence: 99%